The Effect of Green Development Models on Business Sustainability in Property Companies in the Digital Age - Suwandi (International Journal of Social Science and Business, 2022)
Recently, the global scenario has changed radically due to the ongoing coronavirus disease pandemic and the economic impact caused by lockdowns in various countries. It seems that embracing digitalization and the transformation of business organizations that integrate digital technology has become paramount to the survival of enterprises. This study aims to analyze the effect of the Green Development Model on Business Sustainability in Property Companies in the Digital Era. This research is included in descriptive quantitative research. This research was conducted on Property, and Real Estate Companies registered on the IDX. The sampling technique in this study is purposive sampling, so the sample obtained in this study was 42 Property and Real Estate companies. Validity and reliability tests are carried out to ensure that the measurements used are accurate and reliable . The dependent construct R-square is used to analyze the effect of the specific independent variable on the dependent latent variable, which displays the magnitude of the effect. Business Sustainability is affected by the Green Development Model. This study’s results show the effect of the Green Development Model on Business Sustainability. The t-statistic value is greater than the beta score. So the explanation above will show that the Green Development Model significantly affects Business Sustainability. A real estate company that also implements the Green Development Model is a form of Business Sustainability that is currently implemented, so it is very influential between the Green Development Model on Business Sustainability.